Development of a non-contact and non-destructive laser speckle imaging system for remote sensing of anisotropic deformation around fastener holes. (April 2020) - Pang, Yong; Chen, Bernard K.; Liu, Wencheng; Yu, Siu Fung; Lingamanaik, Siva N.
Abstract: Strain sensing around the fastener holes is fundamentally significant in structural health monitoring and failure detections. Conventional non-destructive testing (NDT) techniques typically have limitations in performing reliable and efficient inspections. Here, a laser speckle imaging system (LSIS) has been developed to achieve non-contact, non-destructive and remote strain sensing. Methods for determining optimal laser speckle patterns have been investigated to achieve remote sensing of strain up to a working distance of 5 m. This LSIS was applied to study the anisotropic properties of un-notched and circular notched specimens in cold-rolled aluminium sheet, an important material for the construction of lightweight aircraft structures. The results showed that strain distributions determined by LSIS are consistent with finite element (FE) predictions in which the evolution of strain concentrations not only depends on the notch size but also on material anisotropy. This study demonstrates the potential application of LSIS as an effective NDT technique for full-field, non-contact and remote sensing of anisotropic deformation around fastener holes. Highlights: Laser speckle imaging sensor (LSIS) for remote strain sensing has been successfully developed. The effects of wavelength and f-ratios on and laser speckle size were experimentally studied. Anisotropic strain distribution measured by LSIS are consistent with finite element prediction. The technical feasibilities of LSIS for in-situ structural health monitoring are demonstrated.